Research methods and statistics in psychology - Haslam, S. Alexander; McGarty, Craig (Singapore : Sage, 2019)
A comprehensive introduction to both quantitative and qualitative research methodologies in Psychology, the book guides readers through every step of the research process, and comes with helpful online resources and videos.
Introduction -- Research in psychology : objectives and ideals -- Research methods -- Experimental design -- Survey design -- Descriptive statistics -- Some principles of statistical inference -- Examining differences between means : the t-text -- Examining relationships between variables : correlation -- Comparing two or more mean by analysing variances : ANOVA -- Analysing other forms of data : chi-square and distribution-free tests -- Classical qualitative methods -- Contextual qualitative methods -- Research ethics -- Conclusion: Managing uncertainty in psychological research -- Appendix A: Writing research reports in psychology -- Appendix B: Areas under the standard normal curve -- Appendix C: Answers in exercises.
Drugo izdanje 2014.
Keywords: Psychology -- Research -- Methodology; Psychometrics; Psychology -- Research -- Methodology; Psychometrics